2002
DOI: 10.1093/carcin/23.1.171
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) in bile duct-cannulated rats: Stereoselective metabolism and tissue distribution

Abstract: 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) is a chiral compound, and the primary metabolite of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), a major carcinogen in tobacco smoke. The goal of the present work was to study the pharmacokinetics and stereoselective metabolism and tissue retention of NNK and NNAL in the rat. Groups of rats were dosed with [5-(3)H]NNK (n = 3) or racemic [5-(3)H]NNAL (n = 3) at a target dose of 8.45 micromol/kg and were killed at selected time points for tissue colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…Previous studies indicated that NNK was preferentially converted to ( S )-NNAL in rats (6, 7). ( S )-NNAL had a large volume of distribution, and was selectively retained in the lung, while ( R )-NNAL was extensively glucuronidated and excreted in the urine (10, 11). Both NNK and NNAL can be metabolically activated by cytochrome P450-catalyzed α-hydroxylation, and POB- and PHB-DNA adducts are formed exclusively from their corresponding precursors, as shown in Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that NNK was preferentially converted to ( S )-NNAL in rats (6, 7). ( S )-NNAL had a large volume of distribution, and was selectively retained in the lung, while ( R )-NNAL was extensively glucuronidated and excreted in the urine (10, 11). Both NNK and NNAL can be metabolically activated by cytochrome P450-catalyzed α-hydroxylation, and POB- and PHB-DNA adducts are formed exclusively from their corresponding precursors, as shown in Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
“…Our results in this study fully supported this hypothesis, and indicate that the sequestration of ( S )-NNAL not only occurs in the lung, but also in other target tissues of NNK. In fact, Wu et al (10) showed the presence of ( S )-NNAL in liver and kidney 24 h after NNK or NNAL administration, although higher concentrations were found in the lung. Our results suggest extensive distribution and retention of ( S )-NNAL, possibly at receptor sites, in various extra-hepatic tissues including pancreas, nasal and oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NNK is considered one of the most potent lung carcinogens in tobacco products [18,19]. Wu et al [20] have revealed a novel persistent activity of NNK with an interchangeable conversion between NNK and its cell metabolites. Chhabra et al [21] have shown that gavage of rodents with NNK results in the formation of DNA-adducts in the mammary gland.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that NNK is rapidly converted to NNAL in vivo and that NNAL has similar carcinogenic potency to NNK in the rat lung (Hecht, 1998), an investigation of the kinetics of P450 2A3-and 2A13-mediated NNAL metabolism was warranted. Finally, the metabolism of individual NNAL enantiomers by P450s 2A3 and 2A13 was investigated because the metabolism and disposition of NNAL in animals and humans is profoundly affected by the absolute stereochemistry of the carbinol carbon (Hecht, 1998;Hecht et al, 2002;Wu et al, 2002). Thus, the effect of carbinol-carbon stereochemistry on the regioselectivity of metabolism by these P450s may provide important information about active-site architecture.…”
mentioning
confidence: 99%